THE INFLUENCE OF PRODUCT ATTRIBUTES AND DIGITAL MARKETING ON FEMALE PURCHASE DECISION OF COSMETICS IN MANADO - Ariananda, Shanon Eunike; Mangantar, Maryam; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2021)
Cosmetics becomes a primary need for most women, cosmetics comprise a range of products that are used to care for and enhance the appearance of the face and body. Women not only using cosmetics to attract the attention of people but because for women beauty is an asset. This study aims to partially and simultaneously analyse the impact of product attributes and digital marketing influencing female purchase decision of cosmetics in Manado. This study uses Quantitative Methods and analyses the research data using Multiple Linear Regression analysis. The sample of this research is female who often buys and uses cosmetics in Manado. The data in this study consisted of primary data that is use questionnaires that were distributed to female consumers that purchasing cosmetics in Manado. The results of this study proved that Product Attributes and Digital Marketing have a significant and positive influence on female Purchase Decisions of cosmetics in Manado partially and simultaneously.Keyword: product attributes, digital marketing, purchase decision